The Influence of Seafaring Experience, Fishermen's Productive Assets and Livelihood Diversification on Fishermen's Welfare in Singkuang Village, Mandailing Natal Regency - Willia Wahyuni; Imsar Imsar; M. Syahbudi (Indonesian Journal of Islamic Economics and Finance, 2026)
This study examines the effects of seafaring experience and productive assets on fishermen’s welfare, with livelihood diversification serving as an intervening variable. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires administered to 98 fishermen in Singkuang Village, Mandailing Natal Regency. The findings reveal that seafaring experience and productive assets have positive and significant effects on livelihood diversification and fishermen’s welfare. Livelihood diversification also has a positive and significant effect on fishermen’s welfare (β = 0.293, p < 0.001). Furthermore, productive assets significantly influence livelihood diversification (β = 0.347, p < 0.001) and fishermen’s welfare (β = 0.441, p < 0.001), while seafaring experience significantly affects livelihood diversification (β = 0.392, p < 0.001) and fishermen’s welfare (β = 0.366, p < 0.001). The structural model demonstrates substantial explanatory power, with an R² value of 0.440 for livelihood diversification and 0.794 for fishermen’s welfare, indicating that the model explains 79.4% of the variance in fishermen’s welfare. These findings suggest that enhancing fishermen’s work experience, strengthening productive assets, and promoting livelihood diversification are effective strategies for improving the sustainable welfare of coastal fishing households.